A Remote Reading Literacy for Senior High School: A Voice from Students - Fauziah Ratna Hapsari (Universitas PGRI Semarang, 2021)
The pandemic Covid-19 outbreak caused reading literacy to get less attention than the normal school condition in SMA Negeri 2 Semarang. Therefore, there should be ways to run remote reading literacy strategies. This study aimed to investigate students' perception toward a remote reading literacy strategy, particularly the reading texts, learning process, advantages and disadvantages of the remote reading literacy strategy. The population of this study was 36 students of the 12th graders in SMA Negeri 2 Semarang. The study design was qualitative descriptive. The data was collected through questionnaires and interview. Then, the data was analyzed using interpretive descriptive analysis. The specific target to be achieved in this study is that by knowing the students' perception of remote reading literacy, the result may be used to reference the English teachers to have the reading literacy in English lesson. The study results were the students' perception that they needed to read an average of five times before reading aloud the texts with the tangible pronunciation and comprehend the meaning of the new vocabularies. Moreover, they informed that the learning process was unique, promoted autonomous learning. However, the video compressing and the internet connection were challenging for the students.